2020
DOI: 10.1080/1061186x.2019.1710157
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal delivery of hydrophobic RAMBAs provides good bioavailability and significant enhancement of retinoic acid signalling in neuroblastoma tumour cells

Abstract: Retinoid treatment is employed during residual disease treatment in neuroblastoma, where the aim is to induce neural differentiation or death in tumour cells. However, although therapeutically effective, retinoids have only modest benefits and suffer from poor pharmacokinetic properties. In vivo, retinoids induce CYP26 enzyme production in the liver, enhancing their own rapid metabolic clearance, while retinoid resistance in tumour cells themselves is considered to be due in part to increased CYP26 production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(87 reference statements)
1
3
0
Order By: Relevance
“…In this study we used cationic liposomes, having previously found that related cationic formulations are effective in drug delivery in culture and in vivo and are poor activators of the complement system 60,61 . Our previous work on RAMBA chemicals that are similarly hydrophobic to the present oxidovanadium complexes, also showed very effective payload delivery by liposomes in under 24 h, and others describe this occurring in under 6 h 48,62,63 . We demonstrated here in this proof-of-principle study that the liposomal delivery approach for oxidovanadium complexes works well under cell culture conditions.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this study we used cationic liposomes, having previously found that related cationic formulations are effective in drug delivery in culture and in vivo and are poor activators of the complement system 60,61 . Our previous work on RAMBA chemicals that are similarly hydrophobic to the present oxidovanadium complexes, also showed very effective payload delivery by liposomes in under 24 h, and others describe this occurring in under 6 h 48,62,63 . We demonstrated here in this proof-of-principle study that the liposomal delivery approach for oxidovanadium complexes works well under cell culture conditions.…”
Section: Discussionsupporting
confidence: 59%
“…AL3 was chosen for this liposomal testing since it was the most hydrophobic and demonstrated the greatest cytotoxicity and differentiative potential. AL3 was incorporated into liposomes derived from DOPC, a neutral lipid used to promote stable lamellar structures, cholesterol to increase stability of the liposomes, and DOTMA as a cationic lipid to improve uptake in mammalian cells 48 . Liposomes containing AL3 were cationic with an average charge of 64 ± 3 mV, a mean diameter of 159 ± 16 nm and polydispersity index of 0.33 ± 0.04.…”
Section: Al1-4-induced Responses Are Not Driven By Their Organic Ligamentioning
confidence: 99%
“…Retinoids induce CYP26 enzyme production in the liver, enhancing their own rapid metabolic clearance, while retinoid resistance in tumor cells occurs in part due to increased CYP26 production. RA-metabolism-blocking agents, which inhibit CYP26 enzymes, can improve RA pharmacokinetics in preclinical NB models [22]. The signaling networks through which RA mediates NB differentiation were inhibited upon MYCN overexpression, which revealed opposing regulation of RA and for a number of differentiation-relevant genes, including LMO4, CYP26A1, ASCL1, RET, FZD7, and DKK1 [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings naturally raise the interesting question whether retinyl esters might also be CYP26A1 substrates. Moreover, retinoic acid metabolism blocking agents (RAMBAs) hold promise for improving the clinical benefit of retinoid treatments, for instance against acute promyelocytic leukemia or neuroblastoma tumors; and interestingly, some of these compounds are esters [ 18 , 19 ]. We expect that the new and convenient proluciferin-based activity assays presented in this study will be useful for the identification of new substrates and inhibitors of CYP26A1.…”
Section: Discussionmentioning
confidence: 99%